REKONSTRUKSI SEJARAH DALAM KUMPULAN PUISI DARI BATAVIA SAMPAI JAKARTA MELALUI PEMBACAAN JAUH BERBASIS KORPUS - Bintang Purwaramdhona, Ananda; Hidayatullah, Mochamad Irfan; Rahayu, Lina Meilinawati (Paradigma: Jurnal Kajian Budaya, 2023)
By applying the mixed research methods combining new historicism and digital humanities with AntConc-assisted distant reading techniques, this research aims to explore a reconstruction of Jakarta's history offered in From Batavia to Jakarta (1619–1999), a collection of poems by Zeffry J. Alkatiri. Results show that history can be reconstructed through the physical structure of narrative poetry represented by the dominant usage of pronoun "they" and intra-sentence conjunctions and prepositions such as "and", "in", and "the" instead of licentia poetica which can violate language rules. However, in the structural analysis, AntConc was not able to detect several linguistic aspects such as typography, figures of speech, metaphors, hyperboles, and personifications in several subchapters, so manual analysis was still required. Results show that the reconstruction of Jakarta’s history by Alkatiri revolves around four main themes, i.e. violence, the struggle against colonialism, Betawi and peranakan cultures, and Jakarta as a city, each of which is imbued with issues pertaining to identity, such as race, class, and urban lifestyle. This reconstruction also features the words "child" and "person" as markers of certain identities.